Pengembangan Inventori MBTI Sebagai Alternatif Instrumen Pengukuran Tipe Kepribadian - Eko Susanto; Mudaim Mudaim (Universitas Mathla'ul Anwar Banten, 2017)
Projection approach is one way to read the personality type by looking at the response of the stimulus abstract tendencies were given. Another approach is an objective approach, which is presented in the form of a statement or statements themselves are often called inventory. One well-known inventory is inventory Myer-Briggs Type Indicator (MBTI). This study aims to develop an instrument identifying personality types and suitability for high school career. The model consists of three stages: (1) identification of needs, (2) design prototypes, and (3) testing the prototype. Product MBTI instrument adapted from preexisting. Product development is directed at the use of specifications for high school students. So that the language in the editorial revision and made a simple form. From the results of early trials are items less read by high school students. The second test item can already be read and understood by the students as a whole. Although it is the end product of research they may do further studies to test the reliability of the instrument developed.